PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN DALAM RUMAH TANGGA DI INDONESIA - Siti Maisyaroh Debi Retno Safitrih; Muhamad Chaidar (Fakultas Ilmu Sosial dan Humaniora, 2026)
Legal protection for children who are victims of domestic violence represents the state’s responsibility to ensure the fulfillment of childer’s rights to safety,as a vulnerable group are often subjected to physicial, psychologicial, sexsual abuse, and neglect by parents or other familiy member, This study aims to analyze the forms of violence against children, the avaible and the ostacles in theair implementation in of Law Number 23 of 2004 on the Elimination of domestic Violence and Law Number 35 of 2014 on Chilid Protection, legal protection is preventive and repressive. The preventive approach includes the formulations of policies, legal educations and the strangthening of chilid protection institutions while the repressive approach involves law enforcement victim recovery and the provision of restitution. Although the legal framework is relatively strong its effectiveness remains constrained by patriarchal culture, weak institutional coordination, adw low public legal awareness Therefore it is necessary to optimize the roles of law enforcemebnt officers chilid protection institutions and socienty in creating a comprehensive and just protection system for chilidren who are victims of domestic violence.